2020
DOI: 10.14336/ad.2020.1104
|View full text |Cite
|
Sign up to set email alerts
|

Of Cross-immunity, Herd Immunity and Country-specific Plans: Experiences from COVID-19 in India

Abstract: India has witnessed a high number of COVID-19 cases, but mortality has been quite low, and most cases have been asymptomatic or mild. In early April, we had hypothesized a low COVID-19 mortality in India, based on the concept of cross-immunity. The presence of cross-immunity is presumed to lead to a milder course of disease and allow the time necessary for the development of adaptive immunity by the body to eliminate the virus. Evidence supporting our hypothesis has started showing up. Multiple studies have sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 20 publications
(18 reference statements)
3
21
0
Order By: Relevance
“…It was also possible for the absence of IgM and IgG antibodies, which were capable of connecting to the virus and preventing it from entering the host cell [ 66 ], in the acute and convalescent serum of the reinfected patients [ 67 ]. Although neutralizing antibodies and memory B and T cells again some common human coronaviruses (HCoV) such as HCoV-229E and HCoV-OC43 were also suggested to confer cross-immunity against SARS-CoV-2 [ 68 ], a report based on data on 150 patients showed that the presence of serum IgM and IgG was not significantly associated with a lower rate of disease recurrence (OR = 0.92, 95% CI = 0.27–3.16) [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was also possible for the absence of IgM and IgG antibodies, which were capable of connecting to the virus and preventing it from entering the host cell [ 66 ], in the acute and convalescent serum of the reinfected patients [ 67 ]. Although neutralizing antibodies and memory B and T cells again some common human coronaviruses (HCoV) such as HCoV-229E and HCoV-OC43 were also suggested to confer cross-immunity against SARS-CoV-2 [ 68 ], a report based on data on 150 patients showed that the presence of serum IgM and IgG was not significantly associated with a lower rate of disease recurrence (OR = 0.92, 95% CI = 0.27–3.16) [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results, ultimately, point to both India's overconfidence in March 2021 based on confirmed reported cases during January/February of this year that the country had managed to control the pandemic 1,2 , and its misreading of these data to mean that a high fraction of the Indian population had acquired immunity to the virus, possibly via cross-immunity gained through exposure to other infections 13 . Our present results show firstly the fallacy of relying on just -indutibly also underreported -confirmed case data to make this assessment given that we estimate the ratio of symptomatic (and presumably confirmed) to total infectious cases, including asymptomatic infections, to be 1: just over 2 (compare Figure 1b and 1c), meaning that a great deal of hidden infection was still ongoing in India when the national government deemed that the country was out of danger and began to open up the economy.…”
Section: Mainmentioning
confidence: 94%
“…Herd immunity could be the only option for Yemen. Given the low mortality due to COVID-19 in cash strapped Yemen, a country specific strategy will be necessary to minimize the burden on the healthcare system and the population in general ( Chakrabarti et al, 2020 ). This is especially true since the recent high-level UN international pledging event for Yemen has been “disappointing”.…”
Section: Covid-19: Is Herd Immunity the Only Option For Fragile Yemementioning
confidence: 99%